Feasibility of a Modified Biopsy Needle for Irreversible Electroporation Ablation and Periprocedural Tissue Sampling. (December 2016) - Wimmer, Thomas; Srimathveeravalli, Govindarajan; Silk, Mikhail; Monette, Sebastien; Gutta, Narendra; Maybody, Majid; Erinjery, Joseph P.; Coleman, Jonathan A.; Solomon, Stephen B.; Sofocleous, Constantinos T.
Objectives: To test the feasibility of modified biopsy needles as probes for irreversible electroporation ablation and periprocedural biopsy. Methods: Core biopsy needles of 16-G/9-cm were customized to serve as experimental ablation probes. Computed tomography-guided percutaneous irreversible electroporation was performed in in vivo porcine kidneys with pairs of experimental (n = 10) or standard probes (n = 10) using a single parameter set (1667 V/cm, ninety 100 µs pulses). Two biopsy samples were taken immediately following ablation using the experimental probes (n = 20). Ablation outcomes were compared using computed tomography, simulation, and histology. Biopsy and necropsy histology were compared. Results: Simulation-suggested ablations with experimental probes were smaller than that with standard electrodes (455.23 vs 543.16 mm 2 ), although both exhibited similar shape. Computed tomography (standard: 556 ± 61 mm 2, experimental: 515 ± 67 mm 2 ; P = .25) and histology (standard: 313 ± 77 mm 2, experimental: 275 ± 75 mm 2 ; P = .29) indicated ablations with experimental probes were not significantly different from the standard. Histopathology indicated similar morphological changes in both groups. Biopsies from the ablation zone yielded at least 1 core with sufficient tissue for analysis (11 of the 20). Conclusions: A combined probe for irreversible electroporation ablation and periprocedural tissue sampling from the ablation zone is feasible. Ablation outcomes are comparable to those of standard electrodes.